PENGARUH PEMAHAMAN MATERI ILMU TAJWID (PADA HUKUM BACAAN MAD) TERHADAP BACAAN AL-QUR’AN SANTRIWATI PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS VIII MTs. PONPES SYAFA’ATURRASUL KEC. KUANTAN TENGAH KAB. KUANTAN SINGINGI - Khairunnisa Khairunnisa; Sopiatun Nahwiyah; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2023)
Studying recitation material has a good understanding cognitively but also the ability to read the Qur'an who capable in motor or practical aspects. At MTs Ponpes Syafa'aturrasul, recitation material has been studied by class VIII students in the Al-Qur'an Hadith subject in odd semesters. However, regarding the reading of the Qur'an, the students found the following symptoms: (1) The students had difficulty reading mad layyin and mad 'aridh lissukun when waqf in reading the Qu'ran. (2) There are female students who read Mad 'Iwad with a length of 4 or 6 harakat. (3) There arefemale students who do not apply the Mad 'Iwad reading law. (4) There are female students who make mistakes in reading the lines/punctuation marks on the letters with the Mad Layyin law. Based on these symptoms, this study aims to determine whether there is an effect of understanding the material of Tajwid Science (on the law of Mad reading) on ​​the reading of the Qur'an for students of class VIII MTs Ponpes Syafa'aturrasul, Central Kuantan District, Kuantan Singingi Regency. This research is a causal associative quantitative type with data collection techniques in the form of tests, documentation, observations, and interviews. While the data analysis using Simple Linear Regression technique. The results of the study indicate that there is no effect of understanding the material of Tajwid Science (variable X) on the reading of the Qur'an for Santriwati (variable Y) class VIII at MTs Ponpes Syafa'aturrasul, Kec. Central Kuantan, Kuantan Singingi Regency. This can be seen in the results of the T test where the tcount value -0.923 is smaller than the ttable value of 1.988. In addition, it can also be seen at the significance value (Sig.) 0.358 Probability 0.05 so that it can be concluded that there is no effect of variable X on variable Y in the study